2022
DOI: 10.3174/ajnr.a7456
|View full text |Cite
|
Sign up to set email alerts
|

Early Ultrasonic Monitoring of Brain Growth and Later Neurodevelopmental Outcome in Very Preterm Infants

Abstract: BACKGROUND AND PURPOSE:In infants born very preterm, monitoring of early brain growth could contribute to prediction of later neurodevelopment. Therefore, our aim was to investigate associations between 2 early cranial ultrasound markers (corpus callosum-fastigium and corpus callosum length) and neurodevelopmental outcome and the added value of both markers in the prediction of neurodevelopmental outcome based on neonatal risk factors and head circumference in very preterm infants. MATERIALS AND METHODS:This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
1
3
1
Order By: Relevance
“…Our study showed that very and moderately preterm preschoolers aged 3-6 years old were at a higher risk of DCD, which is similar to previous studies that showed poor motor performance was common in very preterm children with very low birth weight [39,40]. Consistent with other reports, an increased risk of motor impairment was reported in children born very preterm at or before 32 weeks [10,[41][42][43].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study showed that very and moderately preterm preschoolers aged 3-6 years old were at a higher risk of DCD, which is similar to previous studies that showed poor motor performance was common in very preterm children with very low birth weight [39,40]. Consistent with other reports, an increased risk of motor impairment was reported in children born very preterm at or before 32 weeks [10,[41][42][43].…”
Section: Discussionsupporting
confidence: 92%
“…Preterm infants are born during a particularly vulnerable phase of brain development and are therefore at a significantly higher risk of suboptimal brain development and adverse neurodevelopmental outcomes, including motor, neurosensory, cognitive, and behavioral deficits [40,46]. Previous studies have consistently reported an association of brain microstructure with motor impairments in preterm populations [39,[47][48][49]. Impaired cerebellar development is an important determinant of adverse motor outcomes in very preterm infants [48], and studies have reported an association between fine motor skills and the volume and maturity of the cerebellum, brainstem and gray matter [50].…”
Section: Discussionmentioning
confidence: 99%
“…cUS studies of very preterm infants have shown positive relationships between the CCL at birth, TEA and 2 months’ post-term and motor development, and between the CCL at TEA and cognitive development, at 2 years 28 29. Anderson et al showed that slower CCL growth between 2 and 6 weeks’ PNA was predictive of motor delay and cerebral palsy at 2 years, and Beunders et al showed that slower CCL growth between birth and 2 months’ post-term was related to poorer motor development 24 29. In the current study, we found no evidence to support relationships between the CCL and motor development.…”
Section: Discussioncontrasting
confidence: 86%
“…We excluded infants with major brain injury, in contrast to the study by Anderson et al , which is more likely to predict motor impairment 24 28. The study by Beunders et al excluded infants with any brain injury, although it examined brain growth over a longer period (up to 24 weeks after birth) compared with the first 8 weeks after birth in our study 29…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation